The Integration of Geochemical Characteristics and Stable Isotopes Analyses of δ2H and δ18O in the Paleogene Carbonate Rocks Unit of the M-Field, Ciputat Sub-Basin, North West Java Basin, Indonesia - Syarif Kurniawan; Hendarmawan Hendarmawan; Yoga A. Sendjaja; Euis Yuningsih (Jurnal Geologi dan Sumberdaya Mineral, 2020)
The Paleogene carbonate unit in the North West Java Basin has no cropped out and never been shown in the regional stratigraphy, whether as a formation or as a member of the existing formation. This paper provides new insight of the diagenetic process evidence by the stable isotope of 2H and 18O in formation fluids integrated with petrographic and geochemical data of rock and fluids samples analysis. The major minerals of this carbonate unit are: calcite, clay minerals, dolomite, quartz, plagioclase, and pyrite. From ICP-OES analyses result this carbonate rocks has the content of Fe, Mg and Al ranges 450-7800 ppm, 497-10892 ppm and 96-3900 ppm respectively, while Si and Sr are relatively low around 0.1 ppb to 0.7 ppm and 60 ppm to 570 ppm respectively. Formation water chemistry data shows the total charges for cation and anion were relatively balanced from 75.5 to 396.8 meq, the TDS from 4,904 mg/l to 22,351 mg/l, and SG from 1.005 to 1.016 and were dominated by elements of Na, Ca, Mg, Cl and HCO3. The δ2H and δ18O from water samples are between -26.2 to -37.2 (‰) and between -3.63 to 2.50 (‰) respectively. With all the correlation of geochemical and isotope data of both rock and water indicate that the Paleogene Carbonate system in the M-Field has been through at least once uplifting and one sea water rise/drowning event, with meteoric water affected diagenetic process. These geological processes shown by the calcite cementation, the presence of pyrite and quartz, recrystallization of the carbonate grains and mylonitic dolomite, high content of Mg, Fe and Al, and also the abruptly change of the δ13C and δ18O values.Keywords: Paleogene carbonate, geochemistry, water chemistry, stable isotope, diagenesis.